2014
DOI: 10.1183/09031936.00113214
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors and miRNAs that regulate fetal to adultCFTRexpression change are new targets for cystic fibrosis

Abstract: The CFTR gene displays a tightly regulated tissue-specific and temporal expression. Mutations in this gene cause cystic fibrosis (CF). In this study we wanted to identify trans-regulatory elements responsible for CFTR differential expression in fetal and adult lung, and to determine the importance of inhibitory motifs in the CFTR-3′UTR with the aim of developing new tools for the correction of disease-causing mutations within CFTR.We show that lung development-specific transcription factors (FOXA, C/EBP) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 52 publications
(73 reference statements)
4
82
0
1
Order By: Relevance
“…The cell lines Beas2B (human pulmonary epithelial cells) and Cos7 (transformed African green monkey kidney fibroblasts), from ATCC (www.atcc.org), were maintained in culture as previously described [13,14].…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell lines Beas2B (human pulmonary epithelial cells) and Cos7 (transformed African green monkey kidney fibroblasts), from ATCC (www.atcc.org), were maintained in culture as previously described [13,14].…”
Section: Cell Linesmentioning
confidence: 99%
“…Western blotting was performed as previously described using Cos7 cells plated in 6-well plates (200,000 cells/well) and anti-CFTR MM13-4 (#05-581 Millipore) or anti-Lamin A/C (#05-714 Millipore) primary antibodies [14]. Relative intensities of equal areas were compared using the Quantity One® quantification analysis software (Bio-Rad).…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it will be a very exciting development when miRNA-modulating drugs for CF advance to the stage of clinical studies. A second point worth considering is the relevance of the findings of VIART et al [14] beyond CF. Separate sets of studies have clearly shown that cigarette smoke affects CFTR and miRNA expression.…”
mentioning
confidence: 99%
“…Interestingly, miR-101 directly interacts with CFTR mRNA 3 0 -UTR in combination with an overlapping ARE. 96 Moreover, in addition to miR-145, two additional miRs (miR-150 and miR-451) have also been found to have a developmental effect, being significantly upregulated in the adult lung compared with fetal lung, and therefore contributing to downregulation of CFTR. 105 Because F508del-CFTR is poorly folded, the mutant protein elicits an UPR, thereby inducing Endoplasmic reticulum (ER) stress and subsequent activation of the ER stress signaling cascades.…”
Section: Regulation Of Cftr By Mirnasmentioning
confidence: 99%